Utility of Agnikarma in Day to-Day Practice (International Journal of Ayurveda and Pharma Research, 2025)
Agnikarma is an important para surgical procedure used in Ayurveda widely accepted for pain management since ages. The therapy includes the controlled transfer of varied degree of heat to the affected part with wide therapeutic intentions. Acharya Sushruta, the pioneer of Agnikarma stresses on multifaceted utility of Agnikarma and mentioned that it could be a potential alternative when management using medicine surgery or Kshara fails. He claims non-recurrence of benign pathologies when treated by Agnikarma. Though one can be fascinated by these claims, deeper understanding of the procedure is much essential to achieve the success. As therapy requires fire which could be hazardous and end up in burns. Thus, it is very essential to analyze Agnikarma vidhi in depth and understand logic behind selection of ideal patient, choosing the right device and conducting the procedure without any un toward event with proper precautions. Also knowing the idea behind contraindications allows us to prevent complications in current era. So here is an attempt to understand the rationality behind the various steps included in Agnikarma.